Astrin is required for the maintenance of sister chromatid cohesion and centrosome integrity. - Thein, K; Kleylein-Sohn, J; Nigg, E; Gruneberg, U (2007)
Faithful chromosome segregation in mitosis requires the formation of a bipolar mitotic spindle with stably attached chromosomes. Once all of the chromosomes are aligned, the connection between the sister chromatids is severed by the cysteine protease separase. Separase also promotes centriole disengagement at the end of mitosis. Temporal coordination of these two activities with the rest of the cell cycle is required for the successful completion of mitosis. In this study, we report that depletion of the microtubule and kinetochore protein astrin results in checkpoint-arrested cells with multipolar spindles and separated sister chromatids, which is consistent with untimely separase activation. Supporting this idea, astrin-depleted cells contain active separase, and separase depletion suppresses the premature sister chromatid separation and centriole disengagement in these cells. We suggest that astrin contributes to the regulatory network that controls separase activity.